Laminate and method for manufacturing the same
Patent Information
- Application Number
- JP2022093020
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-08
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2042-06-08
AI Technical Summary
Conventional thermally conductive materials face challenges in achieving high thermal conductivity and reliability, particularly when used with silicon-based heating elements, and existing laminates struggle to provide efficient heat dissipation structures.
A laminate structure comprising multiple particle alignment layers with varying thermally conductive particles and low-melting point metal particles, aligned at predetermined intervals, utilizing a combination of materials such as silicon, aluminum, and copper, with specific particle size ratios and binder resins to enhance thermal conductivity and reliability.
The laminate achieves high thermal conductivity and improved reliability, effectively dissipating heat through directional conduction paths with low thermal resistance and stress relaxation, suitable for electronic devices.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a laminate and a method for manufacturing a laminate. [Background technology]
[0002] In various electronic devices, such as LSIs (Large Scale Integrations), prolonged exposure to high temperatures due to heat generated by the components can lead to malfunctions or failures. Therefore, thermally conductive materials are widely used to prevent the LSI from overheating. These thermally conductive materials prevent the device from overheating by diffusing the heat generated by the components or by transferring it to a heat dissipation component that releases it to the atmosphere or other external environment.
[0003] When metals or ceramics are used as such thermally conductive materials, problems arise such as difficulty in weight reduction, poor processability, or low flexibility. Therefore, various thermally conductive materials based on polymer materials such as resins or rubber have been proposed. For example, a thermally conductive adhesive has been proposed that includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, wherein the metal filler consists of silver powder and solder powder, the solder powder exhibits a melting temperature lower than the thermosetting temperature of the thermally conductive adhesive, and reacts with the silver powder under the thermosetting conditions of the thermosetting adhesive to produce a high-melting-point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent is a curing agent having flux activity toward the metal filler, the curing component is a glycidyl ether type epoxy resin, and the curing agent is a monoanhydride of tricarboxylic acid (see, for example, Patent Document 1). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Patent No. 5796242 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, in the prior art described in Patent Document 1 above, while the heat spreader in the heat dissipation structure can achieve high thermal conductivity through metal bonding, the heat-generating element (electronic component) in the heat dissipation structure is often made of silicon or the like, making it difficult to achieve high thermal conductivity through metal bonding.
[0006] The present invention aims to solve the aforementioned problems in the conventional era and achieve the following objectives. Specifically, the present invention aims to provide a laminate and a method for manufacturing a laminate that can achieve high thermal conductivity and improved reliability. [Means for solving the problem]
[0007] The means to solve the aforementioned problem are as follows: <1> Substrate and A first particle alignment layer is provided on the substrate, which contains first heat-conducting particles, the first heat-conducting particles being aligned at predetermined intervals, A second particle alignment layer is provided on the first particle alignment layer, the second particle alignment layer containing second heat-conducting particles, the second heat-conducting particles being aligned with predetermined spacings apart, It has, A portion of the first heat-conducting particles contained in the first particle alignment layer and a portion of the second heat-conducting particles contained in the second particle alignment layer are in contact, and the volume-average particle size of the first heat-conducting particles is smaller than the volume-average particle size of the second heat-conducting particles. The laminate is characterized in that the substrate contains at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. <2> The ratio (A:B) of the volume-average particle size A of the first heat-conducting particle to the volume-average particle size B of the second heat-conducting particle is 1:2 to 1:50. <1> This is the laminate described in [reference]. <3> The volume-average particle size of the first heat-conducting particle is 0.3 μm or more and 30 μm or less, <1> from <2> It is a laminate described in any of the following. <4> The volume-average particle size of the second heat-conducting particle is 1 μm or more and 100 μm or less. <1> from <3> It is a laminate described in any of the following. <5> The present invention has a third particle alignment layer between the substrate and the first particle alignment layer, the third particle alignment layer containing first low-melting-point metal particles, the first low-melting-point metal particles being aligned with predetermined spacings apart. <1> from <4> It is a laminate described in any of the following. <6> The first particle alignment layer and the second particle alignment layer are further having a fourth particle alignment layer containing second low-melting-point metal particles, wherein the second low-melting-point metal particles are aligned at predetermined intervals apart. <1> from <5> It is a laminate described in any of the following. <7> The first heat-conducting particle and the second heat-conducting particle are at least one of copper particles, silver-coated particles, and silver particles. <1> from <6> It is a laminate described in any of the following. <8> The low melting point metal particles include Sn and at least one selected from Bi, Ag, Cu, and In. <5> from <7> It is a laminate described in any of the following. <9> On the second particle alignment layer, there is a counter substrate facing the substrate, The opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. <1> from <8> It is a laminate described in any of the following. <10> A first particle alignment layer formation step is to form a first particle alignment layer on a substrate containing first heat-conducting particles aligned at predetermined intervals, A second particle alignment layer formation step is to form a second particle alignment layer on a first particle alignment layer, in which a second heat-conducting particle is aligned with a predetermined distance between them. Includes, The manufacturing method of a laminate, characterized in that the base material contains at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics.
Advantages of the Invention
[0008] According to the present invention, the above-mentioned various problems in the prior art can be solved, the above-mentioned object can be achieved, a laminate with high thermal conductivity and improved reliability and a manufacturing method thereof can be provided.
Brief Description of the Drawings
[0009] [Figure 1] FIG. 1 is a schematic view showing an example of a laminate according to the first embodiment. [Figure 2] FIG. 2 is a schematic view showing an example of a laminate according to the second embodiment. [Figure 3] FIG. 3 is a schematic view showing an example of a laminate according to the third embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an example of a heat dissipation structure used in the present invention.
Modes for Carrying Out the Invention
[0010] (Laminate) The laminate of the present invention has a base material, a first particle alignment layer, and a second particle alignment layer, preferably has a third particle alignment layer and a fourth particle alignment layer, and further has other layers as required.
[0011] In the present invention, by having a base material, a first particle alignment layer containing first heat-conducting particles and having the first heat-conducting particles aligned at predetermined intervals on the base material, and a second particle alignment layer containing second heat-conducting particles and having the second heat-conducting particles aligned at predetermined intervals on the first particle alignment layer, a heat conduction path in the vertical direction can be efficiently formed. Even for a base material with poor solder wettability composed of at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics, it can achieve low thermal resistance, excellent stress relaxation, high thermal conductivity, and can significantly improve reliability.
[0012] <Base material> There are no particular restrictions on the shape, structure, size, material, etc. of the base material, and it can be appropriately selected according to the purpose. Examples of the shape of the base material include a plate shape, a sheet shape, etc. Examples of the structure of the base material include a single-layer structure, a laminated structure, etc. The size of the base material can be appropriately selected according to the application, etc. The material of the base material is a material with poor solder wettability and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, alumina, gallium nitride, etc. Examples of the mold resin include epoxy resin, silicone resin, urethane resin, acrylic resin, etc. There are no particular restrictions on the average thickness of the base material, and it can be appropriately selected according to the purpose. The base material may be the heat-generating body (electronic component) itself in the heat dissipation structure.
[0013] <First particle alignment layer> The first particle alignment layer preferably contains first heat-conducting particles and a binder resin, and further contains other components as required. The first heat conductive layer is preferably formed on the substrate and in contact with the substrate, and more preferably the first heat conductive particles are in contact with the substrate.
[0014] -The first heat-conducting particle- The first heat-conducting particles are preferably at least one of copper particles, silver-coated particles, and silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the first heat-conducting particle is not particularly limited and can be appropriately selected depending on the purpose. Examples include spherical, flattened, granular, and needle-shaped particles. The volume-average particle size of the first thermal conductive particle is preferably 0.3 μm or more and 30 μm or less, and more preferably 0.5 μm or more and 10 μm or less. When the volume-average particle size of the thermal conductive particle is 0.3 μm or more and 30 μm or less, high thermal conductivity and low thermal resistance can be achieved. The aforementioned volume-average particle size can be measured, for example, using a laser diffraction / scattering particle size distribution analyzer (product name: Microtrac MT3300EXII).
[0015] -Binder resin- The binder resin contains a film-forming resin, a curable resin, and a curing agent.
[0016] The film-forming resin is not particularly limited and can be appropriately selected depending on the purpose. Examples include phenoxy resin, unsaturated polyester resin, saturated polyester resin, urethane resin, butadiene resin, polyimide resin, polyamide resin, and polyolefin resin. These may be used individually or in combination of two or more.
[0017] The curable resin is not particularly limited and can be appropriately selected depending on the purpose. Examples include epoxy resins, oxetane compounds, and (meth)acrylates.
[0018] -Epoxy resin- The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose. Examples include glycidyl ether type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A type epoxy resin, trisphenol type epoxy resin, tetraphenol type epoxy resin, phenol-xylylene type epoxy resin, naphthol-xylylene type epoxy resin, phenol-naphthol type epoxy resin, phenol-dicyclopentadiene type epoxy resin, alicyclic epoxy resin, and aliphatic epoxy resin. These may be used individually or in combination of two or more types.
[0019] -Oxetane compounds- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups. The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl) ether, and 1,4-bis(3-ethyl-3-oxetanylmethyl) Examples include xy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyl oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyl oxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), and bis[(3-ethyl-3-oxetanyl)methyl] isophthalate (OXIPA). These may be used individually or in combination of two or more.
[0020] -(meth)acrylate- The (meth)acrylate is not particularly limited and can be appropriately selected depending on the purpose. Examples include methyl acrylate, ethyl acrylate, isopropyl acrylate, isobutyl acrylate, phosphate acrylate, epoxy acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane triacrylate, dimethylol tricyclodecane diacrylate, tetramethylene glycol tetraacrylate, 2-hydroxy-1,3-diacroxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxyethoxy)phenyl]propane, dicyclopentenyl acrylate, tricyclodecanyl acrylate, tris(acryloxyethyl) isocyanurate, and urethane acrylate. Furthermore, methacrylates derived from these acrylates are also available. These may be used individually or in combination of two or more.
[0021] -Hardening agent- There are no particular restrictions on the curing agent, and it can be appropriately selected depending on the purpose. Examples include imidazoles, organic peroxides, anionic curing agents, cationic curing agents, and organic acids. Examples of the imidazoles mentioned above include 2-ethyl-4-methylimidazole. Examples of the aforementioned organic peroxides include lauroyl peroxide, butyl peroxide, benzyl peroxide, dilauroyl peroxide, dibutyl peroxide, peroxydicarbonate, and benzoyl peroxide. Examples of the anionic curing agents include organic amines. Examples of the cationic curing agents include sulfonium salts, onium salts, and aluminum chelating agents. Examples of the organic acid include glutaric acid and succinic acid. The curing agent may also be glutaric anhydride, a compound modified from succinic anhydride, or a metal salt of an organic acid such as silver glutarate.
[0022] -Other ingredients- The first particle alignment layer may contain other components as long as they do not impair the effects of the present invention. The other components are not particularly limited and can be appropriately selected depending on the purpose, and examples include antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, and flame retardants.
[0023] -The alignment state of the first heat-conducting particles- In the present invention, the first particle alignment layer contains first heat-conducting particles aligned with predetermined spacings between them. It is preferable that the first heat-conducting particles are in contact with the substrate in order to achieve high thermal conductivity. The fact that the first particle alignment layer contains first heat-conducting particles aligned with predetermined spacings can be confirmed, for example, by cutting the cured material, polishing the resulting cut surface, and examining the polished surface with a semiconductor inspection microscope.
[0024] Preferably, the first heat-conducting particles are arranged in a regular pattern that repeats a predetermined arrangement in a plan view of the first particle alignment layer. For example, the arrangement of the first heat-conducting particles can be a square lattice arrangement in a plan view of the first particle alignment layer. Other examples of the regular arrangement of the first heat-conducting particles include lattice arrangements such as rectangular lattices, orthorhombic lattices, hexagonal lattices, and triangular lattices. The arrangement of the first heat-conducting particles may also be a combination of multiple lattices of different shapes. As an example of the arrangement of the first heat-conducting particles, rows of particles arranged linearly at predetermined intervals may be placed in parallel at predetermined intervals. Regions in which the first heat-conducting particles are densely arranged and regions in which they are sparsely arranged may be regularly repeated. It is preferable that the first heat-conducting particles are individually independent and spaced apart from one another in order to improve thermal conductivity. Furthermore, the arrangement also includes a configuration in which multiple first heat-conducting particles are linked or closely spaced to form a unit, and these units are regularly arranged. When the first heat-conducting particles are arranged in a regular manner, the lattice axis or arrangement axis of the arrangement may be parallel to or intersect with at least one of the longitudinal direction and the direction perpendicular to the longitudinal direction of the first particle alignment layer.
[0025] The interparticle distance of the first heat-conducting particles is not particularly limited and can be appropriately selected depending on the purpose. For example, the nearest neighbor particle distance is preferably 0.5 times or more the volume-average particle size of the first heat-conducting particles, and more preferably 0.7 times or more. On the other hand, the nearest neighbor particle distance is preferably 100 times or less the volume-average particle size of the first heat-conducting particles, and more preferably 50 times or less.
[0026] The number density of the first heat-conducting particles is 100 particles / mm³. 2 The above is preferable, with 300 pieces / mm 2 More than 70,000 pieces / mm 2 The following is more preferable: 6,000 pieces / mm 2 More than 45,000 pieces / mm 2 The following is even more preferable.
[0027] The average thickness of the first thermal conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 μm to 100 μm, and more preferably 1 μm to 30 μm.
[0028] <Second particle alignment layer> The second particle alignment layer is formed on the first particle alignment layer. The second particle alignment layer contains second heat-conducting particles aligned at predetermined intervals, preferably contains a binder resin, and may further contain other components as needed.
[0029] -The second heat-conducting particle- The second heat-conducting particle is preferably at least one of copper particles, silver-coated particles, and silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the second heat-conducting particle is not particularly limited and can be appropriately selected depending on the purpose, for example, spherical, flattened, granular, needle-shaped, etc. A portion of the first heat-conducting particles contained in the first particle alignment layer and a portion of the second heat-conducting particles contained in the second particle alignment layer are in contact, and it is necessary that the volume-average particle size of the first heat-conducting particles is smaller than the volume-average particle size of the second heat-conducting particles. If the volume-average particle size of the first heat-conducting particles is larger than the volume-average particle size of the second heat-conducting particles, the thermal conductivity may decrease. The ratio (A:B) of the volume-average particle size A of the first heat-conducting particle to the volume-average particle size B of the second heat-conducting particle is preferably 1:2 to 1:50, and more preferably 1:10 to 1:40. The volume-average particle size of the second thermal conductive particle is preferably 1 μm or more and 100 μm or less, more preferably 10 μm or more and 70 μm or less, and even more preferably 10 μm or more and 50 μm or less. When the volume-average particle size of the second thermal conductive particle is 1 μm or more and 100 μm or less, high thermal conductivity and low thermal resistance can be achieved. The volume-average particle size of the second heat-conducting particle can be measured in the same manner as the volume-average particle size of the first heat-conducting particle.
[0030] -Binder resin- The binder resin in the second particle alignment layer is the same as the binder resin in the first particle alignment layer, so its explanation is omitted.
[0031] -Other ingredients- The other components in the second particle alignment layer are the same as those in the first particle alignment layer, so their explanation is omitted.
[0032] -The alignment state of the second heat-conducting particle- The alignment state of the second heat-conducting particles is the same as that of the first heat-conducting particles in the first particle alignment layer described above, so its explanation is omitted.
[0033] The average thickness of the second thermal conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 20 μm to 300 μm, and more preferably 20 μm to 100 μm.
[0034] <Third particle alignment layer> Preferably, the third particle alignment layer is formed between the substrate and the first particle alignment layer. The third particle alignment layer contains first low-melting-point metal particles aligned at predetermined intervals, preferably contains a binder resin, and may further contain other components as needed.
[0035] -First low-melting-point metal particle- As the first low-melting-point metal particles, solder particles specified in JIS Z3282-1999 are preferably used. Examples of the aforementioned solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, and Sn-Ag-Cu solder particles. These may be used individually or in combination of two or more types. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, and Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Ag-Cu solder particles, and Sn-In solder particles are more preferred.
[0036] The shape of the first low-melting-point metal particles is not particularly limited and can be appropriately selected depending on the purpose. Examples include spherical, flattened, granular, and needle-shaped particles. The melting point of the first low-melting-point metal particles is preferably 100°C or more and 250°C or less, and more preferably 120°C or more and 200°C or less.
[0037] The volume-average particle size of the low-melting-point metal particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 μm or less, and more preferably 1 μm or more and 5 μm or less. The volume-average particle size of the low-melting-point metal particles can be measured in the same manner as the volume-average particle size of the heat-conducting particles.
[0038] -Binder resin- The binder resin in the third particle alignment layer is the same as the binder resin in the first particle alignment layer, so its explanation is omitted.
[0039] -Other ingredients- The other components in the third particle alignment layer are the same as those in the first particle alignment layer, so their explanation is omitted.
[0040] -The alignment state of the first low-melting-point metal particles- The alignment state of the first low-melting-point metal particles is the same as the alignment state of the first heat-conducting particles in the first particle alignment layer described above, so its explanation is omitted.
[0041] The average thickness of the third particle alignment layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 μm to 100 μm, and more preferably 1 μm to 50 μm.
[0042] <Fourth particle alignment layer> The fourth particle alignment layer is preferably formed between the first particle alignment layer and the second particle alignment layer. The fourth particle alignment layer contains 12 low-melting-point metal particles aligned at predetermined intervals, preferably contains a binder resin, and may further contain other components as needed.
[0043] -Second type of low-melting-point metal particle- The second low-melting-point metal particles are the same as the first low-melting-point metal particles in the third particle alignment layer described above, so their explanation is omitted.
[0044] -Binder resin- The binder resin in the fourth particle alignment layer is the same as the binder resin in the first particle alignment layer, so its explanation is omitted.
[0045] -Other ingredients- The other components in the fourth particle alignment layer are the same as those in the first particle alignment layer described above, so their explanation is omitted.
[0046] -The alignment state of the second low-melting-point metal particles- The alignment state of the second low-melting-point metal particles is the same as that of the first heat-conducting particles in the first particle alignment layer described above, so its explanation is omitted.
[0047] The average thickness of the fourth particle alignment layer is the same as that of the third particle alignment layer, so its explanation is omitted.
[0048] <Opposite substrate> The opposing substrate is positioned opposite the substrate, and there are no particular restrictions on its shape, structure, size, material, etc., and it can be appropriately selected according to the purpose. Examples of the shape of the opposing substrate include plate-like and sheet-like shapes. Examples of the structure of the opposing substrate include single-layer and laminated structures. The size of the opposing substrate can be appropriately selected depending on the application. The material of the opposing substrate is a material that is easily wetted by solder and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing substrate may be the heat spreader itself in the heat dissipation structure.
[0049] <Other components> Other components are not particularly limited and can be selected as appropriate depending on the purpose, such as intermediate layers and protective layers.
[0050] (Method of manufacturing a laminate) The present invention provides a method for manufacturing a laminate, comprising a first particle alignment layer formation step and a second particle alignment layer formation step, and further including other steps as necessary.
[0051] <First particle alignment layer formation process> The first particle alignment layer formation step is a step of forming a first particle alignment layer on a substrate, which contains first heat-conducting particles aligned at predetermined intervals. The substrate includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. Since the first heat-conducting particles are the same as the first heat-conducting particles contained in the first particle alignment layer, their description is omitted.
[0052] There are no particular limitations on the method for forming the first particle alignment layer containing the first heat-conducting particles arranged at predetermined intervals, and a suitable method can be selected depending on the purpose. For example, a mold can be prepared in which recesses corresponding to the arrangement pattern of the first heat-conducting particles are formed, the first heat-conducting particles can be filled into the recesses of the mold, and a resin layer containing a binder resin formed on a release film can be bonded on top of the first heat-conducting particles to press them in. By doing so, the first heat-conducting particles can be transferred to the resin layer in a predetermined pattern, thereby forming a first particle alignment layer sheet in which the first heat-conducting particles are arranged at predetermined intervals. Next, the first particle alignment layer sheet is placed on the substrate so that the first heat-conducting particles are in contact with it, and then pressed together to form a first particle alignment layer containing the first heat-conducting particles in an aligned state with predetermined spacing between them.
[0053] <Second particle alignment layer formation process> The second particle alignment layer formation step is a step of forming a second particle alignment layer on the first particle alignment layer, in which second heat-conducting particles are aligned with predetermined spacing between them. Since the second heat-conducting particles are the same as the second heat-conducting particles contained in the second particle alignment layer, their description is omitted. The method for forming a second particle alignment layer containing the second heat-conducting particles arranged at predetermined intervals is the same as the method for forming a first particle alignment layer containing the first heat-conducting particles arranged at predetermined intervals, so its explanation is omitted.
[0054] <Other processes> Other processes are not particularly limited and can be selected as appropriate depending on the purpose. Examples include a third particle alignment layer formation process and a fourth particle alignment layer formation process.
[0055] Herein, embodiments of the laminate of the present invention will be described in detail with reference to the drawings. In each drawing, the same reference numerals are used for the same components, and redundant descriptions may be omitted. Furthermore, the number, position, shape, etc. of the components described below are not limited to this embodiment, and may be set to a number, position, shape, etc. that is preferable for carrying out the present invention.
[0056] <First Embodiment> Figure 1 is a schematic diagram showing an example of a laminate according to the first embodiment. The laminate 10 in Figure 1 has, on a base material 11, a first particle alignment layer 12 in which first heat-conducting particles 17 are aligned at predetermined intervals, a third particle alignment layer 14 on the first particle alignment layer in which first low-melting-point metal particles 19 are aligned at predetermined intervals, a second particle alignment layer 13 on the third particle alignment layer in which second heat-conducting particles 18 are aligned at predetermined intervals, a fourth particle alignment layer 15 on the second particle alignment layer in which second low-melting-point metal particles 20 are aligned at predetermined intervals, and a counter base material 16 on the fourth particle alignment layer. A portion of the first heat-conducting particles 17 contained in the first particle alignment layer 12 is in contact with a portion of the second heat-conducting particles 18 contained in the second particle alignment layer 13, and the volume-average particle size of the first heat-conducting particles is smaller than the volume-average particle size of the second heat-conducting particles.
[0057] <Second Embodiment> Figure 2 is a schematic diagram showing an example of a laminate according to the second embodiment. The laminate 10A in Figure 2 has, on a substrate 11, a first particle alignment layer 12 in which first heat-conducting particles 17 are aligned at predetermined intervals, a second particle alignment layer 13 on the first particle alignment layer in which second heat-conducting particles 18 are aligned at predetermined intervals, a fourth particle alignment layer 15 on the second particle alignment layer in which second low-melting-point metal particles 20 are aligned at predetermined intervals, and a counter substrate 16 on the fourth particle alignment layer. A portion of the first heat-conducting particles 17 contained in the first particle alignment layer 12 is in contact with a portion of the second heat-conducting particles 18 contained in the second particle alignment layer 13, and the volume-average particle size of the first heat-conducting particles is smaller than the volume-average particle size of the second heat-conducting particles.
[0058] <Third Embodiment> Figure 3 is a schematic diagram showing an example of a laminate according to the third embodiment. The laminate 10B in Figure 3 has a base material 11, a first particle alignment layer 12 in which first heat-conducting particles 17 are aligned at predetermined intervals, a third particle alignment layer 14 in which first low-melting-point metal particles 19 are aligned at predetermined intervals, a second particle alignment layer 13 in which second heat-conducting particles 18 are aligned at predetermined intervals, and a counter base material 16 on the second particle alignment layer. A portion of the first heat-conducting particles 17 contained in the first particle alignment layer 12 is in contact with a portion of the second heat-conducting particles 18 contained in the second particle alignment layer 13, and the volume-average particle size of the first heat-conducting particles is smaller than the volume-average particle size of the second heat-conducting particles.
[0059] The laminate of the present invention can be suitably used when constructing a power LED module or power IC module by bonding a thermal interface material (TIM), an LED chip, or an IC chip mounted on a heat dissipation substrate to a heat sink, which fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between them. Here, power LED modules come in wire-bonded and flip-chip mounting types, while power IC modules come in wire-bonded mounting types.
[0060] The heat dissipation structure used in the present invention is composed of a heat-generating element, a laminate of the present invention, and a heat dissipation member.
[0061] There are no particular restrictions on the heat-generating element, and it can be appropriately selected according to the purpose. Examples include electronic components such as CPUs (Central Processing Units), MPUs (Micro Processing Units), and GPUs (Graphics Processing Units).
[0062] The heat dissipation member is not particularly limited as long as it is a structure that dissipates the heat generated by electronic components (heat-generating elements), and can be appropriately selected according to the purpose. Examples include heat spreaders, heat sinks, vapor chambers, and heat pipes. The heat spreader is a component for efficiently transferring heat from the electronic component to other components. There are no particular restrictions on the material of the heat spreader, and it can be appropriately selected according to the purpose, for example, copper, aluminum, etc. The heat spreader is usually in the shape of a flat plate. The heat sink is a component for releasing heat from the electronic component into the air. There are no particular restrictions on the material of the heat sink, and it can be appropriately selected depending on the purpose, for example, copper, aluminum, etc. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a direction non-parallel to one surface of the base portion (for example, in a direction perpendicular to it). The heat spreader and the heat sink generally have a solid structure with no internal space. The vapor chamber is a hollow structure. A volatile liquid is sealed inside the hollow structure. Examples of the vapor chamber include a hollow heat spreader, a hollow heat sink, or a plate-shaped hollow structure. The heat pipe is a hollow structure that is cylindrical, substantially cylindrical, or flattened. A volatile liquid is sealed inside the hollow structure.
[0063] Here, Figure 4 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by electronic components 3 such as semiconductor elements, and as shown in Figure 4, it is fixed to the main surface 2a of the heat spreader 2 that faces the electronic components 3, and is sandwiched between the electronic components 3 and the heat spreader 2. In addition, the thermal conductive sheet 1 is sandwiched between the heat spreader 2 and the heat sink 5.
[0064] The heat spreader 2 is formed, for example, in the shape of a rectangular plate and has a main surface 2a facing the electronic component 3 and side walls 2b erected along the outer circumference of the main surface 2a. The heat spreader 2 has a thermal conductive sheet 1 provided on the main surface 2a surrounded by the side walls 2b, and a heat sink 5 is provided on the other surface 2c opposite to the main surface 2a via the thermal conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently it absorbs heat from electronic components 3 such as semiconductor elements. For example, it can be formed using copper or aluminum, which have good thermal conductivity.
[0065] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The heat spreader 2 also has the leading edge of its side wall 2b mounted on the wiring board 6, thereby surrounding the electronic component 3 at a predetermined distance by the side wall 2b. Furthermore, by providing the laminated body 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member is formed that absorbs the heat generated by the electronic component 3 and dissipates heat from the heat sink 5. [Examples]
[0066] The following describes embodiments of the present invention, but the present invention is not limited in any way to these embodiments.
[0067] (Example 1) <Preparation of the first particle alignment layer-forming sheet> - Fabrication of the first particle alignment layer resin film - A resin composition containing 56 parts by mass of oxetane compound (4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by UBE Corporation), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 22 parts by mass of polyamide compound (M1276, manufactured by Arkema Corporation) was applied to a release film (PET38GS, manufactured by Lintec Corporation) to prepare a first particle alignment layer resin film having a resin layer with an average thickness of 15 μm.
[0068] -Preparation of a film-like master disc in which the first heat-conducting particles are aligned- First, a 2mm thick nickel plate is prepared, and cylindrical protrusions (outer diameter 4μm, height 4μm, center-to-center distance 6μm) are formed in a hexagonal lattice pattern over a 50cm square area of the plate, with a surface density of 32,000 protrusions / mm². 2 This was used as the master disc for the transfer. Next, a polyethylene terephthalate (PET) substrate film with a width of 50 cm and a thickness of 50 μm was prepared, and a photocurable resin composition containing 100 parts by mass of acrylate resin (M208, manufactured by Toagosei Co., Ltd.) and 2 parts by mass of photopolymerization initiator (IRGACURE184, manufactured by BASF Japan Ltd.) was applied to the PET substrate film to a film thickness of 30 μm. The obtained photocurable resin composition film is pressed with a nickel transfer disc from its convex surface, and a high-pressure mercury lamp (1,000 mJ / cm²) is applied. 2By irradiating the PET substrate film with light, a photocurable resin layer was formed in which the convex portions of the transfer disc were transferred as concave portions. By continuously repeating this operation while aligning it along the longitudinal direction of the PET substrate film, a film-like master disc of approximately 10 m was obtained in which the convex portions of the transfer disc were transferred as concave portions. The obtained film-like master disc had concave portions arranged in a hexagonal grid pattern, corresponding to the convex portion pattern of the transfer disc. Next, Ag particles (manufactured by DOWA Electronics Co., Ltd., volume-average particle size Dv: 1 μm) were prepared as the first heat-conducting particles, and these first heat-conducting particles were scattered multiple times on the surface of the film-like master disc. Then, the first heat-conducting particles were wiped with a cloth to fill the recesses of the film-like master disc, which had been cut to a length of 30 cm.
[0069] -Transfer of the first heat-conducting particles to the resin film for the first particle alignment layer- Next, the resin film for the first particle alignment layer was placed on a cut film-like master disc filled with the first heat-conducting particles under predetermined conditions, with its longitudinal length matching the width and its width including the central part of the film-like master disc. The first heat-conducting particles were then transferred by pressing at 60°C and 0.5 MPa. The insulating resin layer film was then peeled off from the film-like master disc, and the aligned first heat-conducting particles on the heat-conducting film were pressed into the resin film for the first particle alignment layer by applying pressure (pressure conditions: 60°C to 70°C, 0.5 MPa). This process was repeated at five points on the cut film-like master disc to produce a sheet for forming the first particle alignment layer in which the first heat-conducting particles were embedded in an aligned state.
[0070] <Preparation of the second particle alignment layer formation sheet> - Fabrication of the second particle alignment layer resin film - On a release film (PET38GS, manufactured by Lintec Corporation), a resin composition containing 56 parts by mass of an oxetane compound (4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by UBE Industries, Ltd.), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 22 parts by mass of a polyamide compound (M1276, manufactured by Arkema S.A.) was applied to produce a resin film for a second particle alignment layer having a resin layer with an average thickness of 70 μm.
[0071] In Example 1, a second particle alignment layer forming sheet was produced in the same manner as in Example 1, except that the above resin film for the second particle alignment layer was used and the first heat conductive particles were changed to the second heat conductive particles 1 (Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle diameter Dv: 40 μm).
[0072] <Production of the third and fourth particle alignment layer forming sheets> - Production of resin films for the third and fourth particle alignment layers - On a release film (PET38GS, manufactured by Lintec Corporation), a resin composition containing 56 parts by mass of an oxetane compound (4,4′-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by UBE Industries, Ltd.), 22 parts by mass of glutaric acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 22 parts by mass of a polyamide compound (M1276, manufactured by Arkema S.A.) was applied to produce resin films for the third and fourth particle alignment layers having a resin layer with an average thickness of 20 μm.
[0073] In Example 1, a third and fourth particle alignment layer forming sheet was produced in the same manner as in Example 1, except that the above resin films for the third and fourth particle alignment layers were used and the first heat conductive particles were changed to the first and second low melting point metal particles (Sn 58 Bi 42 particles: manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter Dv: 4 μm, melting point 139 °C).
[0074] <Production of the laminate> A 30mm x 30mm x 2mm base material (silicone) and a 30mm x 30mm x 2mm opposing base material (copper) were layered in the following order from the base material (silicone) side: a first particle alignment layer forming sheet, a third particle alignment layer forming sheet, a second particle alignment layer forming sheet, and a fourth particle alignment layer forming sheet. After performing heat lamination at 80°C in the predetermined positions, a heat press was performed at 80°C for 15 minutes to produce the laminate of Example 1.
[0075] (Example 2) In Example 1, the second particle alignment layer-forming sheet was prepared in the same manner as in Example 1, except that the second heat-conducting particle 1 (Ag-coated Cu particle, manufactured by Fukuda Metal Foil & Powder Industry Co., Ltd., volume-average particle size Dv: 40 μm) was replaced with the second heat-conducting particle 2 (Cu particle, manufactured by Fukuda Metal Foil & Powder Industry Co., Ltd., volume-average particle size Dv=40 μm). The laminate of Example 2 was then prepared in the same manner as in Example 1.
[0076] (Comparative Example 1) A laminate of Comparative Example 1 was prepared in the same manner as in Example 1, except that the first particle alignment layer forming sheet was not provided.
[0077] (Comparative Example 2) A laminate of Comparative Example 2 was prepared in the same manner as in Example 1, except that a second particle alignment layer forming sheet was not provided.
[0078] Next, the thermal conductivity and reliability of each resulting laminate were evaluated as follows. The results are shown in Tables 1 and 2.
[0079] <Thermal conductivity> For each resulting laminate, the thermal resistance (°C·cm) was measured using a method compliant with ASTM-D5470. 2 The thermal resistance (W / m·K) was measured. From the results, the thermal resistance of the base material and the opposing base material was subtracted to calculate the thermal resistance of the cured product. From the thermal resistance and the thickness of the cured product, the thermal conductivity (W / m·K) was determined, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity of 10 W / m·K or higher ○: Thermal conductivity of 7 W / m·K or more and less than 10 W / m·K ×: Thermal conductivity less than 7 W / m·K
[0080] <Vitality> Each of the above laminates was placed in an environmental testing chamber at 150°C for 500 hours for reliability testing. After the test, the thermal conductivity was measured, and the percentage decrease from the initial thermal conductivity was determined. The reliability was then evaluated according to the following criteria. [Evaluation Criteria] ◎: The decrease in thermal conductivity compared to the initial thermal conductivity is less than 10%. ○: The decrease rate from the initial thermal conductivity is between 10% and 30%. ×: The decrease in thermal conductivity is greater than 30% compared to the initial thermal conductivity.
[0081] [Table 1]
[0082] [Table 2] [Industrial applicability]
[0083] The laminate of the present invention can achieve high thermal conductivity as a thermal interface material (TIM), and is therefore suitable for use around various electrical devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature can adversely affect the efficiency and lifespan of the element's operation. [Explanation of Symbols]
[0084] 1. Thermal conductive sheet 2 Heat spreader 2a Main surface 3. Heat-generating element (electronic component) 3a Top side 5 Heatsink 6 Wiring board 7 Laminate 10, 10A, 10B laminate 11 Base material 12. First particle alignment layer 13. Second particle alignment layer 14. Third Particle Alignment Layer 15. The fourth particle alignment layer 16 Opposing substrate 17. The first heat-conducting particle 18. Second heat-conducting particle 19. First low-melting-point metal particles 20 Second low-melting-point metal particles
Claims
1. A substrate; a first particle alignment layer on the substrate, the first particle alignment layer containing first thermally conductive particles, the first thermally conductive particles being aligned at predetermined intervals; a second particle alignment layer on the first particle alignment layer, the second particle alignment layer containing second thermally conductive particles, the second thermally conductive particles being aligned at predetermined intervals; and a portion of the first thermally conductive particles contained in the first particle alignment layer and a portion of the second thermally conductive particles contained in the second particle alignment layer are in contact with each other, and the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles; 1. A laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
2. 2. The laminate according to claim 1, wherein a ratio (A:B) of a volume average particle size A of the first thermally conductive particles to a volume average particle size B of the second thermally conductive particles is 1:2 to 1:
50.
3. The laminate according to claim 1 , wherein the first thermally conductive particles have a volume average particle size of 0.3 μm or more and 30 μm or less.
4. The laminate according to claim 1 , wherein the second thermally conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.
5. 3. A laminate according to claim 1, further comprising a third particle alignment layer between the substrate and the first particle alignment layer, the third particle alignment layer containing first low-melting point metal particles, the first low-melting point metal particles being aligned at a predetermined interval.
6. 3. A laminate according to claim 1, further comprising a fourth particle alignment layer between the first particle alignment layer and the second particle alignment layer, the fourth particle alignment layer containing second low-melting point metal particles, the second low-melting point metal particles being aligned at a predetermined interval.
7. The laminate according to claim 1 , wherein the first thermally conductive particles and the second thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles.
8. The laminate according to claim 5 , wherein the first low-melting-point metal particles contain Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
9. The laminate according to claim 6 , wherein the second low-melting-point metal particles contain Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
10. a substrate facing the substrate and disposed on the second particle alignment layer; 3. The laminate according to claim 1, wherein the opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
11. a first particle alignment layer forming step of forming a first particle alignment layer on a substrate, the first particle alignment layer including first thermally conductive particles spaced apart and aligned at predetermined intervals; a second particle alignment layer forming step of forming a second particle alignment layer on the first particle alignment layer, the second particle alignment layer including second thermally conductive particles spaced apart and aligned at a predetermined interval; Including, 10. A method for producing a laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.